2000
DOI: 10.1108/09513570010316144
|View full text |Cite
|
Sign up to set email alerts
|

The use and representational faithfulness of graphs in Australian IPO prospectuses

Abstract: This paper investigates the use of graphs, selection of variables to graph and construction of graphs in prospectuses issued by Australian companies making their initial public offering (IPO) of shares to the Australian capital market. The paper formulates and tests hypotheses concerning selectivity in the use of graphs and distortion in the construction of graphs presented in IPO prospectuses, as well as providing descriptive evidence about the use of graphs in such prospectuses. Results show that firms enjoy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 18 publications
2
53
0
8
Order By: Relevance
“…A series of studies covering several major countries has found that a significant number of financial graphs exhibited measurement distortion (i.e., the graph's physical measurement is disproportionate to the underlying numbers) (Steinbart, 1989;Beattie and Jones, 1992a, 1992b, 1996Mather et al , 1996Mather et al , , 2000Courtis, 1997;Frownfelter and Fulkerson, 1998). Moreover, certain other design and construction features (e.g., graph type selected, use of background, directional ordering of time series) appear to be manipulated in order to present corporate performance in the best possible light (Beattie andJones, 1992a, 1992b;CICA, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies covering several major countries has found that a significant number of financial graphs exhibited measurement distortion (i.e., the graph's physical measurement is disproportionate to the underlying numbers) (Steinbart, 1989;Beattie and Jones, 1992a, 1992b, 1996Mather et al , 1996Mather et al , , 2000Courtis, 1997;Frownfelter and Fulkerson, 1998). Moreover, certain other design and construction features (e.g., graph type selected, use of background, directional ordering of time series) appear to be manipulated in order to present corporate performance in the best possible light (Beattie andJones, 1992a, 1992b;CICA, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…They show that measurement distortion in excess of 10% is just perceptible to users. Since 1992, there have been a succession of financial graphics studies (e.g., Beattie andJones, 2000 and2001;Courtis, 1997;Frownfelter-Lohrke and Fulkerson, 2001;Mather, Ramsay and Serry, 1996;Mather, Ramsay and Steen, 2000;and Mather, Mather and Ramsay, 2005) all of which have developed, and reinforced, the earlier findings of selectivity, measurement distortion and presentational enhancement.…”
Section: Financial Graphs In Annual Reportsmentioning
confidence: 99%
“…Unfortunately, although the incidence of measurement distortions has been empirically demonstrated on many occasions (see, for example, Steinbart, 1989;Mather et al, 2000), these studies have been conducted without any insight into what level of measurement distortion is generally sufficient to influence a user's perception of a company's performance. As a result, the practical significance of the findings from empirical studies of company practice remains unclear.…”
Section: Introductionmentioning
confidence: 99%